2017
DOI: 10.1007/s40195-017-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Simulation for Rolling of Diamond–Cu Composites

Abstract: We demonstrate an innovative preparation approach of diamond/Cu composites by powder-in-tube technique and rolling. A small copper tube was loaded with Ti-and Cu-coated diamond particles, and then the diamond particles were combined with Cu matrix by composite rolling. The morphology and element distribution of the interface between diamond and Cu were determined by scanning electron microscopy and energy-dispersive spectrometer. Finite element method (FEM) simulation was used to analyze the rolling process as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…To better understand the thermal conduction mechanism in the G f /Al composites, it is essential to establish a TC model with respect to the G f inclination angle. However, most TC models only focused on the volume fraction of reinforcements and did not discuss the inclination angle [19][20][21]. Chen et al [22] established a TC model of h-BNreinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the thermal conduction mechanism in the G f /Al composites, it is essential to establish a TC model with respect to the G f inclination angle. However, most TC models only focused on the volume fraction of reinforcements and did not discuss the inclination angle [19][20][21]. Chen et al [22] established a TC model of h-BNreinforced polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Consequently, extensive research has been conducted on the microstructure, corrosion, and protection of this material. For example, Wang et al 6) examined solidphase diffusion bonding between Q235A and austenitic stainless steel AISI304. They found that brittle compounds segregated to improve the performance of diffusion-welded joints when the welding temperature was controlled at 850°C.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the addition of Nickel (Ni) in steels enlarges the austenite phase region, inhibits bainitic transformation, decreases the ductile-brittle transition temperature, and effectively improves cryogenic impact toughness (CIT) [15][16][17]. In contrast, Chromium (Cr) dissolves into Fe matrix, shrinks the austenite phase region, and promotes bainitic transformation [18].…”
Section: Introductionmentioning
confidence: 99%